APPLICATIONS OF FRACTIONAL CALCULUS FOR SECOND ORDER DIFFERENTIAL EQUATIONS - Yilmazer, Resat (Univ Prishtines, 2019)
Fractional calculus is a very useful and simple means in obtaining particular solutions to certain nonhomogeneous linear differential equations. Our aim in this work is to obtain fractional solutions of the second order nonhomogeneous differential equation with Nishimoto's operator.
Keywords: Fractional calculus; Generalized Leibniz rule; Ordinary differential equation